2012
DOI: 10.1158/0008-5472.can-11-1831
|View full text |Cite
|
Sign up to set email alerts
|

ERK1/2 Regulation of CD44 Modulates Oral Cancer Aggressiveness

Abstract: Carcinogen-induced oral cavity squamous cell carcinoma (OSCC) incurs significant morbidity and mortality and constitutes a global health challenge. To gain further insight into this disease, we generated cell line models from DMBA-induced murine primary OSCC capable of tumor formation upon transplantation into immunocompetent wild-type mice. While several lines grew rapidly and were capable of metastasis, some grew slowly and did not metastasize. Aggressively growing lines displayed ERK1/2 activation, which st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
162
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 182 publications
(181 citation statements)
references
References 48 publications
12
162
0
Order By: Relevance
“…It was also shown in the same study that knockdown of CD44v6 by siRNA decreased prostate cancer cell invasive and adhesive ability to hyaluronic acid (HA), suggesting that CD44v6 is an important participant in mediating tumor cell adhesion during metastasis (3). Another study showed that CD44 was a downstream effector of ERK1/2 inducing cell migration and invasion in vitro and tumor growth and metastasis in vivo in human oral cancer (19). It was reported that CD44v6 induced EMT in prostate cancer and the induction of EMT was accompanied by a shift in CD44 isoforms in breast cancer cells (49).…”
Section: Discussionmentioning
confidence: 98%
“…It was also shown in the same study that knockdown of CD44v6 by siRNA decreased prostate cancer cell invasive and adhesive ability to hyaluronic acid (HA), suggesting that CD44v6 is an important participant in mediating tumor cell adhesion during metastasis (3). Another study showed that CD44 was a downstream effector of ERK1/2 inducing cell migration and invasion in vitro and tumor growth and metastasis in vivo in human oral cancer (19). It was reported that CD44v6 induced EMT in prostate cancer and the induction of EMT was accompanied by a shift in CD44 isoforms in breast cancer cells (49).…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Wang et al indicated that overexpression of activated Erk1/2 and cyclin D1 proteins are involved in oral tongue carcinogenesis (51). Finally, Judd et al (59) reported that MEK1 activation enhances CD44 expression and promotes aggressiveness in HNSCC, while Katada et al (60) and Zuo et al (61) suggested that Erk1/2 activation correlates with increased cell migration and invasion in HNSCC.…”
Section: Discussionmentioning
confidence: 99%
“…MAPK/ERK, one classic downstream signal of the EGFR pathway, could regulate CD44 to modulate tumor aggressiveness (38). The most recent study showed that prostate cancer cell migration and invasion were inhibited by reducing MMP-2/-9 expression via the ROS/ERK pathways (39).…”
Section: Discussionmentioning
confidence: 99%